Fernand Braudel, historiador del autoconocimiento. - Jean Boutier. (Historia Crítica, 2004)
Braudel and his reflections on different temporalities: Braudel and his strong criticism of events. The article traces the rise of events in Braudelian reflection and analyzes the epistemological problems that said position poses for historians. Nonetheless, the different criticisms did not lead Braudel to elimínate events — although he was tempted to do so on various occasions-, but rather to construct them and to organize them in a different way.